HUBUNGAN GAYA BELAJAR SISWA DENGAN HASIL BELAJAR SISWA SMK KONTRUKSI BANGUNAN - Muhammad Alfarazi (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2026)
The purpose of this study was to find out how student learning outcomes in the field of building construction in Vocational High Schools (SMK) relate to student learning styles. Utilizing a literature review based on currently published journals, a survey research design was used. The findings of the analysis showed a strong positive relationship between the learning outcomes of SMK Building Construction students and their preferred mode of learning. These results imply that higher learning outcomes are usually achieved by students who have a better awareness of their learning preferences. These findings imply that when developing learning techniques for vocational building construction, it is imperative to use a learning approach that considers differences in student learning styles. Teachers can apply a more different approach to teaching and improve learning effectiveness and academic success for students by having a deeper understanding of their students' learning styles. Furthermore, this research serves as a foundation for creating a more inclusive teacher preparation program tailored to the learning preferences of SMK Building Construction students.